2021
DOI: 10.1002/pbc.29317
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition at diagnosis and throughout therapy in pediatric patients with solid tumors: A single‐institution study in a developing country

Abstract: Background Changesin nutritional status can constitute a risk factor for reduced tolerance and effectiveness of antineoplastic treatment. Knowledge of the nutritional status of pediatric patients is important for implementing interventions to improve outcomes. We aimed to evaluate nutritional status at diagnosis and throughout therapy in pediatric patients with solid tumors. Objectives To study the prevalence of malnutrition at diagnosis, compare different assessment tools, and examine longitudinal changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
0
7
1
Order By: Relevance
“…ANPEDCancer indicates the measurement of MUAC in all patients, with emphasis on those in whom it is not possible to measure body weight and/or height, as occurs in amputations/disarticulations, important edema or large tumor masses. Several studies reinforce MUAC importance as a good indicator of nutrition status, 1,3,10,15,43,44 especially as a predictor of lean body mass. Totadri et al, 44 developed a nutrition algorithm for children with cancer undergoing chemotherapy and observed that <20% of patients were identified as malnourished by the z scores of weight for height and BMI/A.…”
Section: Discussionmentioning
confidence: 89%
“…ANPEDCancer indicates the measurement of MUAC in all patients, with emphasis on those in whom it is not possible to measure body weight and/or height, as occurs in amputations/disarticulations, important edema or large tumor masses. Several studies reinforce MUAC importance as a good indicator of nutrition status, 1,3,10,15,43,44 especially as a predictor of lean body mass. Totadri et al, 44 developed a nutrition algorithm for children with cancer undergoing chemotherapy and observed that <20% of patients were identified as malnourished by the z scores of weight for height and BMI/A.…”
Section: Discussionmentioning
confidence: 89%
“…19 Patricia reported that the prevalence of different nutritional statuses at diagnosis, calculated according to the Z scores for H/A and BMI/A, was 29.3% malnourished, 49.5% adequate, and 21.2% overweight/ obese in pediatric patients with solid tumors. 24 In Central America, the moderate nutritional depletion proportion reached 18% by arm anthropometry; 45% of patients were severely depleted, and the proportion rose to 59% if serum albumin was added to the assessment criteria. 27 All clinical methods for assessing nutritional status have limitations, particularly in children with cancer, as there is currently no clinical "gold standard."…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of malnutrition according to weight for age, BMI, mid‐upper arm circumference (MUAC), and triceps skin‐fold thickness (TSFT) Z scores were 14.8%, 23.5%, 27.2%, and 21%, respectively 19 . Patricia reported that the prevalence of different nutritional statuses at diagnosis, calculated according to the Z scores for H/A and BMI/A, was 29.3% malnourished, 49.5% adequate, and 21.2% overweight/obese in pediatric patients with solid tumors 24 . In Central America, the moderate nutritional depletion proportion reached 18% by arm anthropometry; 45% of patients were severely depleted, and the proportion rose to 59% if serum albumin was added to the assessment criteria 27 …”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies in pediatric oncology have shown the utility of arm anthropometry in nutritional assessment. 4,6,7,12 The landmark studies from Central America, which showed the adverse clinical implications of malnutrition in children with cancer, incorporated both arm anthropometry and serum albumin as diagnostic criteria. none of these studies conducted a head-to-head comparison of the important clinical outcomes of using the various methods of nutritional assessment.…”
Section: Discussionmentioning
confidence: 99%